Impact of Family Support on Breast Cancer Patient’s Nutritional Status in Jakarta - Yanni, Daffa Arkananta Putra; Wijayanti, Erlina (PSPP JOURNALS, 2024)
Dietary habits significantly influence the risk factors for breast cancer, the most common type of cancer. Family support can greatly impact changes in a patient’s nutritional status. A study conducted in Jakarta aimed to examine the relationship between family support and the nutritional status of breast cancer patients. The researchers employed non-experimental quantitative methods with a cross-sectional design, using purposive sampling to meet specific inclusion and exclusion criteria. Data were analyzed using the chi-square test. The results showed that 9 respondents (29%) had a normal nutritional status, 22 respondents (71%) were overweight, and 25 respondents (80.6%) received strong family support. Although the findings were analyzed, the study ultimately determined that there was no significant association between family support and nutritional status, as indicated by a p-value of 0.320. However, family support remains important for encouraging healthy dietary habits among breast cancer patients and their families.